The GAKhN “Musical Encyclopedia”: Lost in the Fog of History - Bobrik, Olesya (Wiener Slawistischer Almanach, 2026)
The idea of creating a musical Encyclopedia had existed among Russian musicians since the early twentieth century. This is evidenced by the Russian-language edition of Hugo Riemann’s Dictionary of Music in translation and with additions by Iulii Engel′ (1900), numerous articles on music included in The Brockhaus and Efron Encyclopedic Dictionary (1890–1907) and in the Granat Encyclopedic Dictionary (1910–1929). The Musical Encyclopedia project became one of the first discussed at the meetings of the Music Section of GAKhN (1922) and its initiator was Iulii Engel′. According to his plan, the Musical Encyclopedia was to comprise 250 printer’s sheets. Numerous sources, both published and unpublished (preserved mainly in the archive of GAKhN: RGALI, f. 941), indicate that work on the Musical Encyclopedia continued until 1930. Research on the history of the GAKhN Musical Encyclopedia is a kind of scientific detective story, in which numerous facts contradict each other. The most astonishing fact about the history of the GAKhN Musical Encyclopedia is that it disappeared: only 16 articles have been preserved (15 by Ivanov-Boretskii, one by Kuznetsov). All of this raises the question: did the GAKhN Musical Encyclopedia ever exist? This article is dedicated to finding the answer.